Biowaste Treatment and Valorization (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This book focuses on applied technologies on biowaste treatment with the aim to minimize its environmental impact and to recover resources in the form of energy, nutrients, and other valuable products. As a result of this, the book has collected the latest research on mature, conventional, and innovative technologies used to address the challenging issues with the treatment and valorization of different flows of biowaste.